2004
DOI: 10.1590/s1413-86702004000600006
|View full text |Cite
|
Sign up to set email alerts
|

Risk of tuberculosis among household contacts in Salvador, Bahia

Abstract: Household contacts of AFB positive tuberculosis patients have a very high prevalence and risk of tuberculosis infection. TB preventive or therapeutic measures directed towards this group should be implemented in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 9 publications
0
10
0
2
Order By: Relevance
“…Many other authors have highlighted the need to encourage surveillance of contacts as part of the PCT. (20)(21)(22) Since immunity to TB is mediated by cells (macrophages and CD4 T lymphocytes) and not by antibodies, which provide permanent immunity, the existence of an unidentified TB index case will make cure difficult and will favor recurrence among those who are under treatment or were discharged after confirmed cure. (23) The rate of cure and the rate of treatment noncompliance of the cases involving residents of the cities studied who were treated in Brasília were unfavorable, considering the rates recommended by the NMH and, in part, these results could be related to the fact that the patients with TB were treated in a city other than that in which they resided.…”
Section: Discussionmentioning
confidence: 99%
“…Many other authors have highlighted the need to encourage surveillance of contacts as part of the PCT. (20)(21)(22) Since immunity to TB is mediated by cells (macrophages and CD4 T lymphocytes) and not by antibodies, which provide permanent immunity, the existence of an unidentified TB index case will make cure difficult and will favor recurrence among those who are under treatment or were discharged after confirmed cure. (23) The rate of cure and the rate of treatment noncompliance of the cases involving residents of the cities studied who were treated in Brasília were unfavorable, considering the rates recommended by the NMH and, in part, these results could be related to the fact that the patients with TB were treated in a city other than that in which they resided.…”
Section: Discussionmentioning
confidence: 99%
“…2 The extent of the childhood tuberculosis burden is well recognised, but not well quantified in many endemic areas. [4][5][6] A recent survey from Cape Town, South Africa, reported a calculated tuberculosis incidence of 407/100 000/year in children ,13 years of age. 7 In many countries, particularly in sub-Saharan Africa, the tuberculosis epidemic is fuelled by widespread immune compromise resulting from the HIV epidemic.…”
mentioning
confidence: 99%
“…Several reports from different countries have shown that the household contacts (HCs) of patients with active pulmonary TB are at a much higher risk of infection, which ranges from 30 to 80%, depending on the intensity of TB disease transmission (1,2,5,16,24,33,40). Most of the newly infected contacts of patients with TB contain the infection and do not develop disease.…”
mentioning
confidence: 99%